The eye of minds / 1 - Dashner, James, 1972- (Mortality doctrine ;, 2013)
"Michael is a skilled internet gamer in a world of advanced technology. When a cyber-terrorist begins to threaten players, Michael is called upon to seek him and his secrets out"--Provided by publisher.